Molecular and functional profiling unravels targetable vulnerabilities in colorectal cancer - Vlachavas, Efstathios-Iason; Voutetakis, Konstantinos; Kosmidou, Vivian; Tsikalakis, Spyridon; Roditis, Spyridon; Pateas, Konstantinos; Kim, Ryangguk; Pagel, Kymberleigh; Wolf, Stephan; Warsow, Gregor; Dimitrakopoulou-Strauss, Antonia; Zografos, Georgios N.; et al. (Molecular oncology, 2025)
Colorectal cancer (CRC) patients with microsatellite-stable (MSS) tumors are mostly treated with chemotherapy. Clinical benefits of targeted therapies depend on mutational states and tumor location. Many tumors carry mutations in KRAS proto-oncogene, GTPase (KRAS) or B-Raf proto-oncogene, serine/threonine kinase (BRAF), rendering them more resistant to therapies. We performed whole-exome sequencing and RNA-Sequencing of 28 tumors of the Athens Comprehensive Cancer Center CRC cohort, and molecularly characterized CRC patients based on their microsatellite instability (MSI) status, single-nucleotide variations (SNVs)/copy number alterations (CNAs), and pathway/transcription factor activities at the individual patient level. Variants were classified using a computational score for integrative cancer variant annotation and prioritization. Complementing this with public multi-omics datasets, we identified activation of transforming growth factor beta (TGFβ) signaling to be more strongly activated in MSS patients, whereas Janus kinase (JAK)-signal transducer and activator of transcription (STAT) and mitogen-activated protein kinase (MAPK) molecular cascades were activated specifically in MSI tumors. We unraveled mechanisms consistently perturbed in the transcriptional and mutational circuits and identified Runt-related transcription factors (RUNX transcription factors) as putative biomarkers in CRC, given their role in the regulation of pathways involved in tumor progression and immune evasion. Assessing the immunogenicity of CRC tumors in the context of RAS/RAF mutations and MSI/MSS status revealed a critical impact that KRAS mutations have on immunogenicity, particularly in the MSS patient subgroup, with implications for diagnosis and treatment.